Hard Times - Charles Dickens
Coketown is dominated by the figure of Mr Thomas Gradgrind, school owner and model of Utilitarian success. Feeding both his pupils and his family with facts, he bans fancy and wonder from young minds. As a consequence his obedient daughter Louisa marries the loveless businessman.